Underwater Sound Filtering - Simic, Ines (Student Undergraduate Research E-journal!, 2016)
The cocktail party algorithm is one of the most used algorithms for source separation of sound. The algorithm aims to find an automated solution for a problem that everyone experiences regularly, namely how to make oneself heard in a noisy environment. The CP algorithm picks up the sound from different microphones, and applies smart filters once the system has determined which sounds originate from the same source.This problem also becomes topical when developing sensors based on passive sonar, for instance for autonomous aquatic drones who have to develop awareness of ships and other possible obstacles on a busy shipping lane.